The Politics of Decentralization in Ghana's Fourth Republic. (9th April 2014) - Debrah, Emmanuel
Abstract: This article assesses how the District Assemblies in Ghana's Fourth Republic have exercised political, administrative, and fiscal powers transferred to them by the central government. It notes that the creation of the assemblies has promoted popular participation and boosted the autonomy of front-line officials in terms of decision-making and the allocation of financial resources at the local level. However, the central government retains the authority to appoint the District Chief Executive and 30 percent of the assembly members. Local governments experience delays in the transfer of funds, an inability to absorb civil servants of decentralized departments into the local culture, and a lack of capacity to raise revenue for development. The article argues that local election of the District Chief Executive and increased allocation of funds to the rural districts would attract entrepreneurs and skilled civil servants who would be able to implement effective decentralization.